1997
DOI: 10.1074/jbc.272.41.26009
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Transcription Factor 1 Binds Selectively in Vitro to Ku Protein and the Catalytic Subunit of the DNA-dependent Protein Kinase

Abstract: Heat shock transcription factor 1 (HSF1) functions as the master regulator of the heat shock response in eukaryotes. We have previously shown that, in addition to its role as a transcription factor, HSF1 stimulates the activity of the DNA-dependent protein kinase (DNA-PK). DNA-PK is composed of two components: a 460-kDa catalytic subunit and a 70-and 86-kDa heterodimeric regulatory component, also known as the Ku protein. We report here that HSF1 binds specifically to each of the two components of DNA-PK. Bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 37 publications
1
44
0
1
Order By: Relevance
“…For this purpose, we chose wortmannin, an agent commonly used as an inhibitor of DNA-PK, a member of the phosphatidylinositol 3-kinase-related kinase family (23,24). DNA-PK has been shown to directly interact with HSF1 in vitro (31,32) and to modulate its activity in vivo (30,31). However, it has yet to be shown whether wortmannin treatment of cells can affect HSF1 activity.…”
Section: Sodium Vanadate Prevents the Stress Potentiation Of Gr Transmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we chose wortmannin, an agent commonly used as an inhibitor of DNA-PK, a member of the phosphatidylinositol 3-kinase-related kinase family (23,24). DNA-PK has been shown to directly interact with HSF1 in vitro (31,32) and to modulate its activity in vivo (30,31). However, it has yet to be shown whether wortmannin treatment of cells can affect HSF1 activity.…”
Section: Sodium Vanadate Prevents the Stress Potentiation Of Gr Transmentioning
confidence: 99%
“…In contrast, cells containing reduced levels of DNA-PK cs showed reduced accumulation of HSP70 during recovery from stress, and these cells were much more sensitive to heat shock-induced apoptosis (31). Direct interaction between HSF1 and Ku or DNA-PK cs has been observed (31,32), along with DNA-PK cs -mediated in vitro phosphorylation of HSF1 (32) in a region of HSF1 known to be negatively regulated by MAPKs (32)(33)(34)(35). Based on the above observations, it can be concluded that wortmannin is an effective inhibitor of DNA-PK.…”
mentioning
confidence: 99%
“…Another protein-protein interaction implicated in regulating DNA-PK function is that between DNA-PKcs and the Lyn tyrosine kinase, which is capable of disrupting the DNA-PKcs/ Ku complex in vitro (Kumar et al 1998). Heat shock transcription factor 1 (HSF1) can also stimulate DNA-PK activity in vitro through a mechanism that involves interactions between HSF1 and Ku and weaker interactions between HSF1 and DNA-PKcs (Peterson et al 1995a;Huang et al 1997). These findings suggest that HSF1 could cooperate with Ku and DNA-PKcs, possibly through stabilizing interactions between the DNA-PK holoenzyme and DNA.…”
Section: Regulation Of Dna-pkmentioning
confidence: 99%
“…Possibly stabilizes interaction between DNA-PK and DNA and may regulate DNA-PK after heat stress Peterson et al (1995); Huang et al (1997) High mobility group proteins 1 and 2 (HMG1 and 2)…”
Section: Dna-pk Interactions Within the Nhej Machinarymentioning
confidence: 99%